Responses of soil arbuscular mycorrhizal fungi to rotational grazing in mixed-sown artificial grasslands - WANG Yuan; MI Yang; GUO Rong; ZHANG Yu; TIAN Xia; WANG Zhanjun; JIANG Qi; YU Hongqian; JI Bo; MA Kun (浙江大学学报. 农业与生命科学版, 2024)
This study investigated the impact mechanism of rotational grazing on vegetation communities and soil arbuscular mycorrhizal (AM) fungal communities in mixed-sown artificial grassland ecosystems. Taking the mixed-sown artificial grasslands in Yanchi County of Ningxia as the experimental subject, we set up three different patterns of mixed-sown combinations using a one-way randomized block design: T1 (Bromus inermis Leyss.+Psathyrostachys juncea Nevski+Festuca rubra+Medicago sativa L.+Cichorium intybus L.), T2 (Elymus nutans Griseb.+Psathyrostachys juncea Nevski+Poa annua L.+Medicago sativa L.+Astragalus cicer L.), and T3 (Agropyron cristatum+Psathyrostachys juncea Nevski+Agropyron mongolioum Keng+Medicago sativa L.). Illumina high-throughput sequencing and bioinformatics analysis were conducted to investigate the differences of AM fungal communities in the three mixed-sown artificial grassland ecosystems under grazing disturbance, and to analyze the relationships among the vegetation communities, soil physicochemical properties and AM fungal communities. The results indicated that two consecutive years of rotational grazing had a significant impact on the biomass of the vegetation communities. Compared with those after the first year of rotational grazing, the relative importance values of the leguminous vegetation communities decreased, but the relative importance values of the gramineous vegetation communities increased by 51.16%, 81.25% and 33.33%, respectively. Throughout both years, Glomus and Paraglomus were the dominant genera of AM fungi in the soil. Compared with that after the first year of rotational grazing, the Chao 1 index of the soil AM fungal community in the T1 treatment significantly decreased by 12.35% after two consecutive years of rotational grazing. Nevertheless, the Chao 1 index, Shannon-Wiener index, evenness index and species number of the soil AM fungal community in the T3 treatment significantly increased by 20.73%, 12.80%, 7.69% and 31.16%, respectively (P＜0.05), which indicates that the soil AM fungal community is more sensitive to grazing intensity during the T3 treatment. The soil AM fungal community structures spatially overlapped between the T1 and T2 treatments and separated between the T1 and T3 treatments with the increase of rotational grazing years. The environmental factors attributed to the alteration of AM fungal communities shifted from available phosphorus (p=0.006) and alkali-hydrolyzable nitrogen (p=0.016) to vegetation community biomass (p=0.036) with the increase of rotational grazing years. After two consecutive years of rotational grazing disturbance, the effects of soil nutrients on soil AM fungal community richness diminished, whereas the effects of vegetation community diversity and biomass on soil AM fungal community richness and composition enhanced. In summary, different types of mixed-sown artificial grassland vegetation communities and soil AM fungal communities exhibit different response characteristics to rotational grazing. Among the three types of mixed-sown artificial grasslands, the combination of T3 is superior.